Understanding the sustainable marketing strategies: Lessons from Milk-White soap- Kanagarajah - Shivany, S. (Eastern University, Sri Lanka with Sri Sathya Sai University for Human Excellence, India, 2023)
Due to rising uncertainties about the impact of business decisions on society and the environment, many companies are forced to practice sustainable marketing strategies. Even though, this concern becomes essential for contemporary firms, all don’t follow the requirements for the sustainability needs of the industry, but there were many small businesses those practiced sustainable marketing strategies many years ago without knowing the conceptual agreement with the components. The milk-white industry was owned by a sole proprietor, late Kanagarajah, who focused on sustainable marketing practices which brought his business to the next level. The milk-white industry contended a traditional business model and practiced its sustainable marketing strategies as a competitive advantage in the market. The survival of traditional businesses has remained low when the generation changed in the long term. There are many good conventional practices that were not correctly understood by the next generation for uplifting their business knowledge. This study aimed to fill the gap by understanding the sustainable marketing practices of a traditional business model run by the late Mr.Kanagarajah. This study used qualitative methodology to explore sustainable marketing practices. Case study strategy was used to collect the data from different sources and thematic analysis was employed to understand the sustainable marketing practices of the selected industry case. This study theorized ecological consciousness, social consciousness, environmental product quality, employee wellbeing, content marketing, and stakeholder involvement as sustainable marketing strategies from a traditional business model findings of this study enrich the knowledge of sustainable marketing in the local context.
Keywords: Sustainable marketing strategies; Ecological consciousness; Social consciousness; Environmental product quality